Estructuración y aplicación del manual de procesos como instrumento para afianzar el modelo de gestión de la empresa Santiago Pérez Investigación y Estudios Cía. Ltda - Pazmiño Santacruz, Andrés (2012)
This project is focused on improving cycle management surveys for which it is necessary to record, analyze and streamline activities, generating activities to promote practices that lead to efficiency and effectiveness, eliminate wasted time, effort and materials and lead to sustain a culture of quality. Emphasising that not enough rules but, further, it is essential to changing attitudes in the entire workforce, in not only do things right, but within the practices defined in the organization. Achieving in this way that compliance with the times and deadlines is the most serious commitment to the company.